Pengangkatan Anak Pada Masyarakat Di Kabupaten Bima Ditinjau Menurut Peraturan Pemerintah Nomor 54 Tahun 2007 - Isdiatul Islamiah; Sahruddin Sahruddin (Private Law, 2022)
This study describes most children adoption practices in Bima Regency, reviewed from Government Regulation No 54 of 2007. It also identifies factors preventing the process according to the regulation from being practiced. This study is an empirical one. Results of this study show that the most children adoption practices in Bima Regency are not according to the regulation. Most foster parents do not submit the adoption application to the court. Thus, the adoption is legally invalid. The lack of legal awareness is the factor preventing the legal adoption practice.